2019
DOI: 10.12991/jrp.2019.180
|View full text |Cite
|
Sign up to set email alerts
|

In vitro cytotoxicity evaluation of Marrubium vulgare L. methanol extract

Abstract: Marrubium vulgare L. (Lamiaceae) is a herbal drug used for centuries for many diseases. In this present study the plant material was acquired from commercial sources in pharma grade (PhEur 8.0) quality. The methanol extract of the aerial parts was evaluated for its in vitro cytotoxic activity by measuring the percentage of viable cells (U87 LN229 and T98G glioblastoma multiforme cell lines) using a luminescence system, and the antioxidant activities by ABTS and DPPH radical scavenging spectrophotometrically. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 14 publications
1
11
0
Order By: Relevance
“…In addition, the methanolic extract of M. vulgare was evaluated for its in vitro cytotoxic activity by measuring the percentage of viable cells’ glioblastoma multiforme cell lines (U87, LN229 and T98G) using a luminescence system. After evaluating the cytotoxicity impact that M. vulgare has on U87 (IC 50 : 270.3 μM), LN229 (IC 50 : 343 μM), and T98G (IC 50 : 336.6 μM) from glioblastoma multiforme cell lines, it was concluded that it is the most efficient in two cell lines, U87 (69.9%) and LN229 (71%) [ 30 ].…”
Section: Applications In Medicine and As Pesticidesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the methanolic extract of M. vulgare was evaluated for its in vitro cytotoxic activity by measuring the percentage of viable cells’ glioblastoma multiforme cell lines (U87, LN229 and T98G) using a luminescence system. After evaluating the cytotoxicity impact that M. vulgare has on U87 (IC 50 : 270.3 μM), LN229 (IC 50 : 343 μM), and T98G (IC 50 : 336.6 μM) from glioblastoma multiforme cell lines, it was concluded that it is the most efficient in two cell lines, U87 (69.9%) and LN229 (71%) [ 30 ].…”
Section: Applications In Medicine and As Pesticidesmentioning
confidence: 99%
“…Aqueous extract 175.00 mg GAE/100 g dry material 23.86 mg QE/100 g dry material [26] Aqueous infusion na 5.08 mg/100 mg dry material [27] Ethanol-water extract (70:30, v/v) 93.42 mg of GAE 23.25 mg of RUE/g of extract [14] Ethanol-water extract (70:30, v/v) 59.87 mg GAE/g dry extract 14.47 mg QE/g dry extract [28] Methanol extract (dry) 44.89 mg GAE/g dry extract 24.60 mg QE/g dry extract [29] Methanol extract 48. .00 mg GAE/g extract 12.05-93.12 mg QE/100 g extract [25,30,31] Microwave assisted extract 61.44 mg of GAE/g of extract 37.70 mg of RUE/g of extract [14] Subcritical…”
Section: Phenolic Content Flavonoid Content Referencesmentioning
confidence: 99%
“…The means of phenolic and flavonoids contents recorded for Moroccan M. vulgare extract were 60.409 mg GAE/g and 33.81 mg CE/g, respectively [ 20 ]. Okur et al [ 21 ] signaled that the German extract showed 48.97 ± 0.82 mg GA/g corresponding to the total phenolic amounts. In the same way, Ouchemoukh et al [ 22 ] showed that the Algerian M. vulgare exhibited an important content of total phenolics and flavonoid, equivalent to 40 mg GAE/g and 10 mg/g, respectively, whereas Amri et al [ 7 ] reported that the M. vulgare extract was richer in flavonoid (45.21 mg/g) than in polyphenols (6 mg GAE/g).…”
Section: Resultsmentioning
confidence: 99%
“…For example, the IC 50 of Tunisian M. vulgare extract in the presence of DPPH was 35 µg/mL and 38 µg/mL reported by Aouadhi et al [ 8 ] and Amri et al [ 7 ], respectively. In addition, Bouterfas et al [ 25 ] showed wide ranges of IC 50 (DPPH) varying from 33.7 to 124 µg/mL of Algerian M. vulgare methanolic extract collected from three sites, while the lowest antioxidant power was observed in Moroccan and German M. vulgare methanoIic extracts where the IC 50 was 2.4 mg/L and 0.8 mg/L and 2.08 and 1.33 mg/mL in the presence of DPPH and ABTS, respectively [ 20 , 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…The evaluation of the anti-cancer activity of plant extracts is essential for safe treatment. Various anti-cancer activity studies with cell lines used in this study are available on plant extracts (Okur et al 2019). OFI fruits are also in the safe range in terms of toxicity because they are consumed as food among the public.…”
Section: Discussionmentioning
confidence: 99%